PERAN ORANG TUA DALAM MENYIKAPI DAMPAK PERKEMBANGAN TEKNOLOGI BAGI ANAK - Ahmad Zubaidi; Hambali Hambali; Sania Nur Hafita (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2021)
This study aims to analyze and examine the role of parents in responding to the development of technology for children. This research method uses a case study approach in Pakuniran Village, Pakuniran District, Probolinggo Regency. Collecting data used by means of surveys, interviews, and documentation. While the data analysis techniques were carried out using data collection, data editing, data presentation and conclusion of research results. The results of this study state that the role of parents in dealing with increasingly sophisticated technological developments is by: understanding all applications on gadgets, providing educational rewards, and providing intensive supervision and assistance. It was found that there is a need for intensive supervision and assistance from parents to reduce and prevent the negative impact of gadgets on children.